Sensitivity, persistence and asymmetric effects in international stock market volatility during the global financial crisis - Vitor Gabriel (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2015)
Financial market volatility is an important element when setting up port- folio management strategies, option pricing and market regulation. The Subprime crisis affected all markets around the world. Daily data of twelve stock indexes for the period of October 1999 to June 2011 are studied using basic GARCH type models. The data were then di- vided into three different sub-periods to allow the behavior of stock market in different sub-periods to be investigated. The following sub-periods are identified: Dot-Com crisis, Quiet and Subprime crisis. This paper revealed that the Subprime crisis turned out to have bigger impact on stock market volatility, namely at sensitivity, persistence and asymmetric effects.
Keywords: G01; G15; 330; global financial crisis; international stock markets; GARCH models; conditional volatility